Intraoperative Neuromonitoring, Nerves at Risk and Staged Thyroidectomy, our Experience on 377 Consecutive Cases: Nerves at risk and staged thyroidectomy in 377 cases - Rossini, Matteo; Cozzani, Federico; Bonati, Elena; Giuffrida, Mario; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2022)
Purpose: The aim of this study was firstly to report the experience of intermittent intraoperative neuromonitoring (I-IONM) and evaluate the impact of loss of signal (LOS) in staged thyroidectomy management.Methods: We retrospectively reviewed patients who underwent total thyroidectomy, performed by a single surgeon in two years. All patients have been subjected to I-IONM. In case of intraoperative loss of signal (LOS), planned total thyroidectomy was always aborted. Six-month follow-up was performed. Postoperative dysphonia was evaluated with VHI-10 score in 3 time settings T1, during hospital stay, T2 after 30 days, T3 after 6 months. Dysphonia has been compared to IONM results to evaluate sensitivity and specificity.Results: 377 patients were included. Incidence of dysphonia was calculated based on the number of nerves at risk (NAR). We evaluated a total of 724 NAR. LOS encountered were 43 cases (5.9% of total NAR), of these 14 were LOS 1 while 29 were LOS 2. 27 patients (3.7% of NAR) presented early post-operative dysphonia with VHI-10 score > 13 (T1), among these 16 had presented LOS at IONM (true positives) while11 had no LOS (false negatives). In T2 and T3 we reported a decrease in true positive cases increasing false positives. Sensitivity at T3 reached 85.7% while specificity and odds ratio were respectively 94.8% and 110.Conclusions: Given the high sensitivity and specificity, IONM should be considered a useful tool for thyroid surgery and its use should be suggested for patients undergoing planned total thyroidectomy. Its right application may cancel the risk of bilateral paralysis.